1. Oblicz wartość wyrażenia:
a) 6x+1 dla: b) 8 - x dla: c) x(7 - x) dla: d) x2 - 4x dla:
x = -4 x = 10 x = 3 x = 1
x = 0 x = -1 x = 7 x = 5
x = -5 x = 1/2 x = -2 x = -3



Odpowiedź :

Odpowiedź:

a) 6*(-4)+1=-24+1=25

6*10+1=60+1=61

6*3+1=18+1=19

6*1+1=6+1=7 i tak dalej

Odpowiedź:

a) 6x +1

dla x= -4 ;  6* (-4) = -24

dla x= 10 ; 6* 10 = 60

dla x = 3 ;  6* 3= 18

dla x = 1 ; 6* 1=6

dla x = 0 ; 6* 0= 0

dla x = -1 ; 6* (-1) = -6

dla x = 7 ; 6*7= 42

dla x = 5 ; 6* 5= 30

dla x = -5 ; 6* (-5) = -30

dla x = 1/2 ; 6*  1/2 = 3

dla x = -2  ; 6*(-2) = -12

dla x = -3 ; 6* (-3) = -18

b) 8 - x

dla x = -4 ; 8- (-4) = 8+4= 12

dla x = 10 ; 8-10= -2

dla x = 3 ; 8-3= 5

dla x = 1 ; 8-1 = 7

dla x = 0  ; 8-0=8

dla x = -1 ; 8- (-1) = 8+1= 9

dla x = 7  ; 8-7= 1

dla x = 5 ; 8-5=3

dla x = -5 ; 8 - (-5)= 8+5= 13

dla x = 1/2 ; 8- 1/2= 7  2/2 - 1/2=  7   1/2

dla x = -2  ; 8- (-2)= 8+2= 10

dla x = -3 ; 8- (-3)= 8+3= 11

c) x(7 - x)

dla x = -4 ; -4(7- (-4)) = -4 (7+4)= -4 * 11 = -44

dla x = 10 ; 10(7-10)= 10* (-3) = -30

dla x = 3 ; 3(7-3)= 3*4= 12

dla x = 1 ;  1(7-1) = 1* 6= 6

dla x = 0 ; = 0

dla x = -1 ; -1 (7 - (-1)) = -1 (7+1) = -1 *8= -8

dla x = 7 ; 7(7-7)= 0

dla x = 5 ; 5(7-5)= 5*2= 10

dla x = -5 ; -5(7-(-5)) = -5 (7+5)= -5 * 12= -60

dla x = 1/2 ; 1/2 (7- 1/2 )= 1/2 ( 6  2/2 - 1/2) = 1/2 * 6  1/2 = 1/2  * 13/2 = 13/4=

= 3  1/4

dla x = -2 ;  -2(7 - (-2)) = -2 (7+2) = -2 * 9 = -18

dla x = -3 ; -3( 7- (-3))= -3(7+3)= -3*10 = - 30

d) x2 - 4x

dla x = -4 ; (-4) ² - 4 (-4)= 16- (-16)= 16+16= 32

dla x = 10 ; 10² - 4 *10= 100 - 40= 60

dla x = 3 ; 3² - 4*3 = 9- 12 = -3

dla x = 1 ; 1² -4 *1 = 1 -4= -3

dla x = 0 ; = 0

dla x = -1 ; (-1)² -4 *(-1) = 1+4= 5

dla x = 7 ; 7² - 4*7 = 49- 28= - 21

dla x = 5 ; 5² - 4*5= 25- 20 = 5

dla x = -5 ; (-5)² - 4*(-5)= 25 +20= 45

dla x = 1/2 ; (1/2)² - 4 * 1/2 = 1/4 - 2= 1/4- 8/4= - 7/4 =  - 1   3/4

dla x = -2 ; (-2) ² - 4* (-2)= 4 - (-8)= 4+8= 12

dla x = -3 ; (-3)² - 4 *( -3)= 9- (-12)= 9+12= 21

Szczegółowe wyjaśnienie:

Inne Pytanie